T Helper Plasticity Is Orchestrated by STAT3, Bcl6, and Blimp-1 Balancing Pathology and Protection in Malaria - Victor H. Carpio; Florentin Aussenac; Lucinda Puebla-Clark; Kyle D. Wilson; Alejandro V. Villarino; Alexander L. Dent; Robin Stephens (iScience, 2020)
Summary: Hybrid Th1/Tfh cells (IFN-γ+IL-21+CXCR5+) predominate in response to several persistent infections. In Plasmodium chabaudi infection, IFN-γ+ T cells control parasitemia, whereas antibody and IL-21+Bcl6+ T cells effect final clearance, suggesting an evolutionary driver for the hybrid population. We found that CD4-intrinsic Bcl6, Blimp-1, and STAT3 coordinately regulate expression of the Th1 master regulator T-bet, supporting plasticity of CD4 T cells. Bcl6 and Blimp-1 regulate CXCR5 levels, and T-bet, IL-27Rα, and STAT3 modulate cytokines in hybrid Th1/Tfh cells. Infected mice with STAT3 knockout (KO) T cells produced less antibody and more Th1-like IFN-γ+IL-21−CXCR5lo effector and memory cells and were protected from re-infection. Conversely, T-bet KO mice had reduced Th1-bias upon re-infection and prolonged secondary parasitemia. Therefore, each feature of the CD4 T cell population phenotype is uniquely regulated in this persistent infection, and the cytokine profile of memory T cells can be modified to enhance the effectiveness of the secondary response.